Association of smoking, alcohol, BMI, and physical activity with colorectal cancer risk in North Borneo’s multiethnic population - Edawati Hamsah; Freddie Robinson; Nirmal Kaur Singh; Firdaus Hayati (Penerbit UMS, 2025)
The onset of colorectal cancer (CRC) the third most prevalent malignancy worldwide, results from the interactions between inherited and lifestyle factors. Therefore, there is ample opportunity to prevent the incidence of colorectal cancer by addressing the modifiable risk factors, which are still inconsistent in the Asian population. This study aims to determine the association between smoking, alcohol consumption, BMI, and physical activities in North Borneo. This is matched case-control research with a ratio of 1:2, and the sample size was matched to two controls (103:206) regarding age, gender, and ethnicity. Statistical significance was p<0.05, which is significant using SPSS. The frequencies, chi-square, and univariate logistic regression were used. The mean age of respondents is 54.47±11.8 years on average. Major indigenous ethnicities contributed more than 20% in the case group, such as Bajau, Kadazan, and Dusun. Other Indigenous ethnicities are less than 20% (Bugis, Brunei, Murut, Sungai, Bisaya, Jawa, Lundayeh, and Rungus). Although there is no correlation between physical activities, alcohol, and smoking, there is evidence that certain factors like smoking have a weaker relationship (OR= 2.209; 95% CI =1.144-4.264) and more significant or enhanced risk of colorectal incidence. We discovered that a strong association exists between BMI and colorectal Cancer. The implication or consideration of this research is that it might be beneficial in lowering the incidence of colorectal cancer, provided that the public health system devises strategies to engage and empower primary care providers by providing substantial resources or by emphasizing the significance of Indigenous populations for a more significant influence on the incidence and prevention of Cancer.